Analisis Kebijakan Pemotongan PPH 23 atas Pengembalian Premi Reasuransi/Komisi Reasuransi - Inawati, Inawati (Syntax Literate, 2025)
Reinsurance companies (reasuradur) carry out risk coverage cooperation with insurance companies (asuradur) by receiving some amount of premium payments (reinsurance premium) from insurance companies (asuradur). Meanwhile, the insurance company will receive a reinsurance commission/ceding commission in the form of a refund premium as an implication of cooperation in the management of risk coverage and joint costs. in the view of insurance companies, the return of ceding premiums/commissions received by the insurer is a "replacement" of costs that should have been borne by the reinsurer for the upfront acquisition costs incurred by the insurer to obtain the policy from the insured. On the other hand, the tax auditor have a different view. According to the tax auditor, the return of the premium given by the reinsurance company is a reward in the form of a commission paid to the insurance company. Ceding commissions are considered as "rewards" for intermediary services because insurers are considered to act as intermediaries between customers and reinsurance companies. Because it is included in intermediary services, according to the tax auditor, reinsure must deduct WHT Art 23.